Psychological Trauma in Khushwant Singh’s Train to Pakistan, Manohar Malgonkar’s A Bend in the Ganges and Chaman Nahal’s Azadi - P.Kavitha; Dr. B.Visalakshi (The journal of contemporary issues in business and government, 2021)
The darkest period in the history of India was called partition. Partition has been popular theme in Indian English literature of 1940’s. India’s independence and the consequences lead to provide realistic story of political hatred and violence of those turbulent days. This article focuses on three partition novels and its horror. Khushwanth Singh’s Train to Pakistan (1956) is the first Indian English novel written in the theme of partition. Manohar Malgonkar’s A Bend in the Ganges (1964) depicts the struggle for Indian independence and its aftermath. Chaman Nahal’s Azadi (1975) recollects all the sources related to Indian history. All the three novels depict the psychological predicaments of Hindus, Muslims and Sikhs.